Is there a relationship between welfare-state policies and suicide rates? Evidence from the U.S. states, 2000–2015. (February 2020) - Rambotti, Simone
Abstract: Suicide is one of the leading causes of death in the United States. The rise in suicide rates is contributing to the recently observed decline in life expectancy. While previous research identified a solid association between economic strain and suicide, little attention has been paid to how specific welfare policies that are designed to alleviate economic strain may influence suicide rates. There is a growing body of research that is using an institutional approach to demonstrate the role of welfare-state policies in the distribution of health. However, this perspective has not been applied yet to the investigation of suicide. In this study, I combine these approaches to analyze the association between two specific policies, Supplemental Nutrition Assistance Program (SNAP) and Earned Income Tax Credit (EITC), and overall and gender-specific suicide rates across the 50 U.S. states between 2000 and 2015. I estimate two-way fixed-effects longitudinal models and find evidence of a robust association between one of these policies – SNAP – and overall and male suicide. After adjusting for a number of confounding factors, higher participation in SNAP is associated with lower overall and male suicide rates. Increasing SNAP participation by one standard deviation (4.5% of the state population) during the study period could have saved the lives of approximately 31, 600 people overall and 24, 800 men. Highlights: Combines economic strain and institutional theory to investigate welfare and suicide. Estimates the relationship across 50 U.S. states, 2000–2015. Uses two-way state and year fixed-effects. SNAP participation is associated with lower overall and male suicide rates. Increasing SNAP participation may reduce suicide during economic downturns.